SOCIAL CLASSES IN THEODORE DREISER’S SISTER CARRIE - Eunike E. Supit; Agustine C. Mamentu; Delli Sabudu (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this study was to reveal how the concept of social class appeared and how it affected the main character and her relationship with others in Theodore Dreiser’s Sister Carrie. This study was made using qualitative approach. In analysing this study, the researcher used M. H. Abraham’s mimetic theory. The result of this research reveal that there are three kinds of social class that the characters mainly grouped into which are the lower, middle, and upper classes. The groupings are made based on the situation of the characters jobs and income, living conditions, social circle and material wealth. Social class affected the main character by changing her point of view as she adapted to live in the late 19th century Industrialized Chicago. This affected her relationship with other people in a way that she would break off her relationship with others if they are no longer useful to her to get what she wants the most which are wealth and fame, which in the end she regretted